Insecticides Currently Used on Vegetables - Susan E. Webb; Philip A. Stansly (EDIS)
This 12-page fact sheet lists many of the common insecticides currently labeled for use on vegetables in Florida. A number of new materials have been registered in the past few years or have had additional crops added to their labels. Some older organophosphate insecticides are now restricted to just a few crops, a result of recent rulings related to the Food Quality Protection Act. Changes continue, thus this listing may not be totally accurate at the time of printing. Written by S. E. Webb and P. A. Stansly and published by the UF Department of Entomology and Nematology, April 2012.